Unilateral Twin Ectopic Pregnancy in a Patient With a History of Multiple Sexually Transmitted Infections - Charles J. Rolle; Clifford Y. Wai; Roger Bawdon; Rigoberto Santos-Ramos; Barbara Hoffman (Hindawi Limited, 2006)
Background. The incidence of unilateral twin ectopic pregnancy is a rare condition. Several factors increase the risk of ectopic pregnancy, the most important of which is pelvic inflammatory disease, followed by operative trauma, congenital anomalies, tumors, and adhesions resulting in anatomically distorted fallopian tubes. We present a case of a woman with a history of four confirmed sexually transmitted infections (STIs) including Chlamydia trachomatis, Neisseria gonorrhoeae, herpes simplex virus 2, and Treponema pallidum. The case illustrates the potential impact of sexually transmitted infections (STIs) on the risk of a twin ectopic pregnancy. Case. A 24-year-old primigravida, presented with an unknown last menstrual period, lower abdominal pain, watery vaginal discharge, and vaginal spotting. During this hospitalization, serum β-HCG testing was 263 mIU/mL and transvaginal ultrasonographic examination suggested a nonviable unilateral twin ectopic pregnancy. At exploratory laparotomy, a 10 cm mass involving the right fallopian tube and ovary was excised. Pathological evaluation of the specimen identified a monochorionic, diamnionic twin ectopic pregnancy within the fallopian tube. Conclusions Patients with a history of multiple (STIs) are known to be at risk for the development of chronic pelvic infection and postinflammatory scarring. The resulting distortion of the normal tubal anatomy leads to an increased risk of an uncommon presentation of ectopic pregnancy.